finalfanatic
New member
- Joined
- Jan 27, 2012
- Messages
- 1
I have the following linear system:
3x + (3/2)y = -(1/2)
9x + 5y = 1
So far, I've done the following...
3x + (3/2)y = -(1/2) multiply by 6...
18x + 2y = = -3 multiply by -1...
-18x - 2y = 3
Then multiply the second equation by 2 to give...
18x + 10y = 1
Add both equations together to eliminate x giving
8y = 4
y = (1/2)
Subbing this back into the second equation
9x + 5(1/2) = 1
9x + (5/2) = 1
So we need to lose 3/2, so (3/2)/9 is 2/16 = 1/13
This means that x = -(1/13) and y = (1/2), is this correct or have I gone wrong somewhere?
3x + (3/2)y = -(1/2)
9x + 5y = 1
So far, I've done the following...
3x + (3/2)y = -(1/2) multiply by 6...
18x + 2y = = -3 multiply by -1...
-18x - 2y = 3
Then multiply the second equation by 2 to give...
18x + 10y = 1
Add both equations together to eliminate x giving
8y = 4
y = (1/2)
Subbing this back into the second equation
9x + 5(1/2) = 1
9x + (5/2) = 1
So we need to lose 3/2, so (3/2)/9 is 2/16 = 1/13
This means that x = -(1/13) and y = (1/2), is this correct or have I gone wrong somewhere?